Monumen Masa Pemerintahan Orde Lama Di Jakarta: Representasi Visual Nasionalisme Soekarno - Toto Sugiarto Arifin (LP2M ISBI Bandung, 2014)
ABSTRACT The construction of the monument of the Old Order in Jakarta is an integrated part of the struggle of the Indonesian nation. This research is a qualitative study with a qualitative descriptive analysis through textual and contextual analysis. Its focused on the spirit and visual representation of the five monu- ments built during the government of the Old Order in Jakarta, those are the Monumen Selamat Datang, Pembebasan Irian Barat, Pahlawan, Dirgantara, and Monumen Nasional (Monas). The Monuments of the Old Order government in Jakarta as a representation of Bung Karno’s thought of Nationalism, are reflected within the construction of the monument in his government. It does not describe a particular ethnicity or class, but it contains the universal properties of Indonesian nation, and the Monas is consider- ed as the center point of the four other monuments. Bung Karno was a leader who had consistent with the ideology he believed; moreover, he had the ability to integrate a variety of ethnicity, class, and ideology. Everything is reflected in the five monuments which were initiated by him, so that Bung Karno can be stated as a model for leadership in Indonesia. Keywords: nationalism, monuments, spirit, visual representation ABSTRAK Pembangunan monumen masa pemerintahan Orde Lama di Jakarta merupakan bagian integral dari perjuangan bangsa Indonesia. Penelitian ini adalah penelitian kualitatif dengan analisis deskriptif kualitatif melalui analisis tekstual dan kontekstual yang difokuskan terhadap spirit dan representasi visual dari lima monumen yang dibangun pada masa pemerintahan Orde Lama di Jakarta, yaitu Monumen Selamat Datang, Pembebasan Irian Barat, Pahlawan, Dirgantara, dan Monumen Nasional (Monas). Monumen masa pemerintahan Orde Lama di Jakarta sebagai representasi Nasionalisme Bung Karno, tercermin dalam pembangunan monu- men di masa pemerintahannya. Monumen ini tidak digambarkan sebagai tokoh, golongan atau ideologi tertentu, tetapi merupakan representasi dari seluruh jiwa rakyat Indonesia dan nilai- nilai kebudayaannya, serta Monas sebagai titik pusat dari keempat monumen lainnya. Bung Karno sebagai seorang pemimpin yang konsisten dengan ideologi yang diyakininya memiliki kemampuan untuk mengintegrasikan berbagai suku, golongan, dan ideologi. Semuanya itu tercermin pada kelima monumen yang digagasnya, sehingga Bung Karno dapat dĳadikan role model bagi kepemimpinan di Indonesia. Kata kunci: Nasionalisme, monumen, spirit, representasi visual